Pengaruh Komunikasi, Motivasi dan Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Binayasa Putra Batara Menara Btn Jakarta - Anggraeni Kusnadi; Wasino Wasino (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to identify that the influence of communication, motivation and leadership on employee perfomance at PT. Binayasa Putra Batara. In this study, the data collecetion technique used was a survey method by distributing questionnaires with a total sample of 123 respondents. The data analysis method used is the SPSS version 24 software method. The result of this study indicate that variables of communication, motivation and leadership have significant influence of employee performance.